Advances in Usability and User Experience : Proceedings of the AHFE 2019 International Conferences on Usability and User Experience, and Human Factors and Assistive Technology, July 24-28, 2019, Washington D.C., USA /: Proceedings of the AHFE 2019 International Conferences on Usability and User Experience, and Human Factors and Assistive Technology, July 24-28, 2019, Washington D.C., USA. (2019) - Unknown
No abstract available